DETERMINANT FACTORS OF DENTAL AND ORAL SELF-CARE FOR ADOLESCENTS IN THE COASTAL AREA OF CILACAP CITY - Salsabilla Alya Ananda Purwanto Putri; Nur Khamilatusy Sholekhah; Arimbi Arimbi (Indonesian Journal of Dentistry, 2023)
Background: The prevalence of oral health problems in Indonesia is 25.9%. The incidence of oral and dental diseases in Central Java in 2019 was recorded at 126,225 cases and 39,759 of them occurred in Cilacap District. Based on data taken from the Kampung Laut Community Health Center, there were a total of 164 confirmed cases of oral health in 2022, dental and oral diseases that are often found in the community include caries and periodontal disease. Oral health care efforts are the main preventive measures to prevent oral disorders in order to avoid oral diseases, which can be carried out by each individual through self-care, such as brushing teeth, using dental floss, and using mouthwash. The purpose of this study was to determine the relationship between factors of knowledge, behavior, attitude, age, gender, parents' occupation, social history, and history of toothache with oral self-care in adolescents at Kampung Laut 1 Senior High School.Method: This type of observational analytic study uses a cross-sectional design. The sample in this study were 82 students. Data collection was carried out by providing questionnaires which were filled out independently by students.Result: The results of the analysis of the relationship between factors of knowledge (p = 0.037), behavior (p = 0.018), attitude (p = 0.046), age (p = 0.037), gender (p = 0.025), parents' occupation (p = 0.049), social history (p = 0.037) and history of toothache (p = 0.018) on dental and oral self-care in adolescents where the p value of each variable is <0.05 which means it is significant.Conclusion: There is a relationship between knowledge, behavior, attitudes, age, gender, parents' occupation, social history and history of toothache on dental and oral self-care in adolescents.